Answer: ![(x+10)^2+(y+6)^2=121](https://tex.z-dn.net/?f=%28x%2B10%29%5E2%2B%28y%2B6%29%5E2%3D121)
Step-by-step explanation:
The equation of a circle in the general form is:
![ax^{2}+by^2+cx+dy+e=0](https://tex.z-dn.net/?f=ax%5E%7B2%7D%2Bby%5E2%2Bcx%2Bdy%2Be%3D0)
The equaton of a circle in standard form is:
![(x-h)^2+(y-k)^2=r^2](https://tex.z-dn.net/?f=%28x-h%29%5E2%2B%28y-k%29%5E2%3Dr%5E2)
Where the center is at <em>(h, k)</em> and <em>r</em> is the radius
To write the equation of a circle from general form to standard form, you must complete the squaare, as you can see below:
1- Given the equation in general form:
![x^{2}+y^2+20x+12y+15=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%2By%5E2%2B20x%2B12y%2B15%3D0)
2- Complete the square:
-Group the like terms and move the constant to the other side.
- Complete the square on the left side of the equation.
- Add the same value to the other side.
Then you obtain:
![(x^{2}+20x)+(y^2+12y)=-15\\(x^2+20x+(\frac{20}{2})^2)+(y^2+12y+(\frac{12}{2})^2)=-15+(\frac{20}{2})^2+(\frac{12}{2})^2\\\\(x+10)^2+(y+6)^2=-15+100+36\\(x+10)^2+(y+6)^2=121](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%2B20x%29%2B%28y%5E2%2B12y%29%3D-15%5C%5C%28x%5E2%2B20x%2B%28%5Cfrac%7B20%7D%7B2%7D%29%5E2%29%2B%28y%5E2%2B12y%2B%28%5Cfrac%7B12%7D%7B2%7D%29%5E2%29%3D-15%2B%28%5Cfrac%7B20%7D%7B2%7D%29%5E2%2B%28%5Cfrac%7B12%7D%7B2%7D%29%5E2%5C%5C%5C%5C%28x%2B10%29%5E2%2B%28y%2B6%29%5E2%3D-15%2B100%2B36%5C%5C%28x%2B10%29%5E2%2B%28y%2B6%29%5E2%3D121)
Answer:
The answer is 125.6
Step-by-step explanation:
C= 2x3.14x20
C=6.28x 20
C= 125.6
Answer:
1080 degrees
180(n-2) = sum of all interior angles
180(6) = 1080
Answer:
27.8% I think
Step-by-step explanation:
In box 1, the reason that justifies the statement, m∠BAD = m∠BAC + m∠CAD, is: angle addition postulate.
<h3>What is the Angle Addition Postulate?</h3>
The angle addition postulate states that the measure of a larger angle equals the sum of smaller angles that make up the larger angle.
∠BAD comprises of ∠BAC and ∠CAD.
Therefore, based on the angle addition postulate, m∠BAD = m∠BAC + m∠CAD.
The missing reason in box 1 would be: angle addition postulate.
Learn more about angle addition postulate on:
brainly.com/question/24782727
#SPJ5